A Feasibility Study for Clinical Implementation of hypo fractionated SBRT Program at a Clinic in an LMIC Using Locally Designed Lung Phantom - Abigail N.M. Quaye, MPhil; Eric C.D.K. Addison, PhD; Ernest Osei, PhD; Afua A. Yorke, PhD (Advances in Radiation Oncology)
Purpose: This study aims to assess the feasibility of implementing a hypofractionated radiation therapy (HFRT) program at the Oncology Directorate of Komfo Anokye Teaching Hospital in Ghana, addressing specific infrastructure limitations that hinder patient care and treatment efficiency. Hence, we conducted a feasibility study to start a HFRT lung stereotactic body radiation therapy (SBRT) program using currently available resources. The goal is to alleviate the burden on patients and health care providers, particularly in the context of limited resources. Methods and Materials: A lung phantom was designed from locally sourced materials consisting of wood slabs to mimic the lung, a perspex tank filled with water for tissue equivalence, and a 3-cm diameter acrylic ball to simulate the tumor. A motion platform was also designed for the phantom to simulate patients breathing in the superior-inferior direction. We acquired 3 computed tomography (CT) scan data sets using a slow CT scan technique for target motions of 0 cm (no_target_motion), 0.5 cm (0.5-cm_target_motion), and 1 cm (1-cm_target_motion) displacements. Treatment plans were generated for each phantom CT image data set using 9-field 6-Mega-Voltage (MV) photon beams in the eclipse treatment planning system. We also generated a treatment plan using an actual patient CT data set to assess the doses to target in the lung and critical organs at risk during a typical lung SBRT treatment. The quality of each treatment plan was evaluated using the near maximum (D2%), near minimum (D98%), mean (Dmean), V100, V95, V90, heterogeneity index (HI), conformity index (CI), the ratio of 50% prescription isodose volume to the PTV volume, (R50%), maximum dose (in % of dose prescribed) at 2 cm from PTV in any direction (D2cm, Gy) and dose-volume-histograms for the planning target volume (PTV). The near maximum (D2%), mean, V5, V10, V15, and V20 values were used as the dose metrics to evaluate the dose to the lung. Maximum dose was used to evaluate the dose to the spinal cord, and the maximum and mean doses were used to evaluate doses to the esophagus, heart, trachea, and ribs. Results: We quantitatively assessed the quality of the phantom treatment plans by calculating the CI, HI, R50%, and D2cm for each plan. The CI values for the PTV for the no_target_motion, 0.5-cm_target_motion, and 1-cm_target_motion are 1.07, 1.08, and 1.06, respectively. The HIs for the PTV for no_target_motion, 0.5-cm_target_motion, and 1-cm_target_motion are 1.20, 1.10, and 1.20 respectively. The R50% for the no_target_motion, 0.5-cm_target_motion, and 1-cm_target_motion are 3.98, 3.86, and 3.82, respectively, and the corresponding D2cm values are 27.30, 31.64, and 30.47, respectively. The CI, HI, R50%, and D2cm values for the PTV using the actual patient CT data set are 1.08, 1.22, 7.1, and 58.7 respectively. Therefore, our data demonstrate good dose conformity and heterogeneity within the PTV, with a sharp dose fall-off for all cases. The point dose measurements made in the phantom also show good agreement with treatment planning data. Conclusions: Our results demonstrate that implementing HFRT using 3-dimensional conformal radiation therapy for lung SBRT is feasible with the current infrastructure of our institution. Although the proposed treatment plan is effective, future research on motion management and image guidance technologies is necessary to optimize treatment fidelity. These findings suggest that HFRT could be a viable option for addressing resource constraints in radiation therapy delivery in similar settings.